ANALISIS LINGKUNGAN PERUSAHAAN SEBAGAI PERENCANAAN STRATEGI BISNIS PADA USAHA KECIL DAN MENENGAH (UKM) DI KOTA DENPASAR - Astiti, Ni Putu Yeni; Gunadi, I Gusti Ngurah Bagus (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2017)
The objective of strategic planning is to establish and improve the business and the company's products to achive company profit and growth target. Internal environment that can be analyzed include several things, as marketing and distribution, research and development factors and engineering, production and operation management factors, company employee resources, finance and accounting, while the external environment which has a influence on the viability of small industries, inflation, economic growth rates, political conditions, government regulations, technological developments, supplier numbers, competitive conditions and market tastes. Research data is collected by interview with related resource, which are the department of Cooperatives and SMEs of Denpasar and association of SMEs. The Department of Cooperatives and SMEs of Denpasar and the association of SMEs is selected as data resource because both are the authorities in the determination of policy, strategy development and development of SMEs. The result of SWOT analysis shows that MSMEs in Denpasar are in Quadrant IV.